Estimating adult mortality in South Africa using information on the year-of-death of parents from the 2016 Community Survey - Mambwe, Chibwe (Centre for Actuarial Research (CARE), 2022)
In developing countries, systems that collect vital statistics are usually inadequate to facilitate the direct estimation of adult mortality. This has necessitated the development of indirect methods such as the orphanhood method. These methods are however limited, i.e., the single-survey approach produces out of date estimates of mortality and the two-survey approach is affected by the differential reporting of orphanhood between two surveys. To avoid these limitations, this research considers an extension of the orphanhood approach pioneered by Chackiel and Orellana (1985) to estimate adult mortality using year-of-death data rather than the conventional form of the orphanhood data. This is because the year-of- death data can be used to produce accurate time locations to which estimates of mortality apply but more important, one can create a synthetic survey from a single survey and hence obtain more recent and accurate estimates of mortality. The single-survey orphanhood method is applied to survey data to obtain estimates of adult mortality and time location. A variation of the two-survey orphanhood method (Timæus 1991b) is also applied to survey data and the synthetic survey that is created from year-of-death data in order to derive estimates of adult mortality. In addition, the age range of respondents is extended down to age O to include year-of-death data from younger respondents on the assumption that underestimating orphanhood due to the adoption effect is minimal. This is done to investigate if the estimates derived from the two-survey method can be improved. Further, a cohort survival method that involves the calculation of a survival ratio for each age group at the first survey and the equivalent older ages groups at the second survey is applied to investigate the possibility of producing useful estimates of adult mortality based on cohort survival. The level and trend in mortality estimates calculated from the single-survey, two - survey and the cohort survival approaches are discussed and compared to the estimates from the Rapid Mortality Surveillance (RMS) which are used as a benchmark for the trend and level of adult mortality in South Africa. The estimates produced using the single-survey method appear too low, while those from the two-survey method appear to be reasonable for the conventional from of the orphanhood data. Extending the two-survey method to include younger respondents produces estimates that are too low indicating that both the conventional form of the orphanhood data and the year-of-death data suffer from the adoption effect. The cohort survival approach produces reasonable estimates that are consistent with the RMS benchmark for both the conventional form of the orphanhood data and year-of-death data.